2017
DOI: 10.1080/15476286.2017.1379645
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing tRNA-dependent mistranslation in human cells

Abstract: High-fidelity translation and a strictly accurate proteome were originally assumed as essential to life and cellular viability. Yet recent studies in bacteria and eukaryotic model organisms suggest that proteome-wide mistranslation can provide selective advantages and is tolerated in the cell at higher levels than previously thought (one error in 6.9 × 10 in yeast) with a limited impact on phenotype. Previously, we selected a tRNA containing a single mutation that induces mistranslation with alanine at proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…In contrast to the concerns addressed by Crick in his "Frozen Accident Theory" (Crick 1968), mistranslation is not catastrophic for cell viability. At levels in the 3-5% range mistranslation has minimal affect on yeast cell viability Lant et al 2017;Berg et al 2019). For some key cellular proteins, 3-5% mistranslation is sufficient to restore viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the concerns addressed by Crick in his "Frozen Accident Theory" (Crick 1968), mistranslation is not catastrophic for cell viability. At levels in the 3-5% range mistranslation has minimal affect on yeast cell viability Lant et al 2017;Berg et al 2019). For some key cellular proteins, 3-5% mistranslation is sufficient to restore viability.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of fidelity at either step can lead to mistranslation. Mistranslation is dramatically increased by tRNA variants that are inaccurately aminoacylated or contain mutations within their anticodon (Geslain et al 2010;Hoffman et al 2017;Lant et al 2017;Berg et al 2017;Zimmerman et al 2018). Nucleotides in the tRNA that are recognized by a specific aaRS are called identity elements and consist of single nucleotides, nucleotide pairs, and structural motifs (de Duve 1988;Hou and Schimmel 1988;Giegé et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Mistranslation is a general feature of the translation process which has a basal error rate of approximately one misincorporated amino acid in every 10 4 to 10 5 codons [55,56]. Many tRNA variants dramatically increase mistranslation in bacterial, fungal, and mammalian cell culture systems [37,39,[57][58][59][60]. For example, we identified a variant of yeast tRNA Pro that results in~5% proteome wide alanine for proline mistranslation with a minimal effect on cell growth in yeast [39].…”
Section: Discussionmentioning
confidence: 97%
“…Unlike other isoacceptors, the anticodon of alanine, serine, leucine and selenocysteine tRNAs has no role in aminoacylation. If mutated and expressed, these tRNA variants could result in mistranslation [37]. We looked for variants with the potential to mistranslate either through mutations to the anticodon or by possessing a G3:U70 base-pair, the major identity element for AlaRS [37][38][39][40].…”
Section: Location Of Variants On the Trna Structurementioning
confidence: 99%
“…Surprisingly, a perfect proteome is not a pre-requisite for cellular viability even in the context of human cells. Lant et al demonstrated that a single tRNA mutant can lead to significant mistranslation in human cells [17]. This was accomplished by expressing an Ala accepting tRNA Pro G3:U70 variant in HEK 293 cells.…”
Section: Mistranslation and Protein Synthesis Quality Controlmentioning
confidence: 99%